Pushover Response of Multi Degree of Freedom Steel Frames - Tayyab Naqash (Civil Engineering Journal, 2020)
Seismic codes use the behaviour factor to consider the ductility and the structure's non-linearity to improve the system's overall performance. Generally, Steel moment-resisting frames are characterized by a relatively high period showing high deformability and, foreseen that with stringent damageability criteria, the adopted behaviour factor might not optimally be utilized for achieving better performance of the frames. The design is generally governed by stiffness, leaving behind a complex structural system where the capacity design rules are disturbed and therefore necessitates to relax the drift limits for such frames. Given this and with extensive parametric analysis, the current paper aims to examine the behaviour factor of steel Moment Resisting Frames (MRFs). The parametric analysis has been conducted on rigid steel MRFs of 9, 7, and 5 storeys with bay 4 different bay widths of 9.15 m, 7.63 m, 6.54 m, and 5.08 m. Perimeter frame configuration has been designed using 4 different behaviour factors (q = 6.5, 4, 3, and 2) for a total number of 144 cases. Static nonlinear analysis has been conducted, and consequently, the behaviour factors have been examined. It has been observed that compatibility is required while choosing the drift limit for an assumed ductility class of the code. Doi: 10.28991/cej-2020-SP(EMCE)-08 Full Text: PDF